3D scanning based mold correction for planar and cylindrical parts in aluminum die casting. Issue 2 (7th January 2015) - Seno, Takashi; Ohtake, Yutaka; Kikuchi, Yuji; Saito, Noriaki; Suzuki, Hiromasa; Nagai, Yukie
Abstract: Aluminum die casting is an important manufacturing process for mechanical components. Die casting is known to be more accurate than other types of casting; however, post-machining is usually necessary to achieve the required accuracy. The goal of this investigation is to develop machining- free aluminum die casting. Improvement of the accuracy of planar and cylindrical parts is expected by correcting metal molds. In the proposed method, the shape of cast aluminum made with the initial metal molds is measured by 3D scanning. The 3D scan data includes information about deformations that occur during casting. Therefore, it is possible to estimate the deformation and correction amounts by comparing 3D scan data with product computer-aided design (CAD) data. We corrected planar and cylindrical parts of the CAD data for the mold. In addition, we corrected the planar part of the metal mold using the corrected mold data. The effectiveness of the proposed method is demonstrated by evaluating the accuracy improvement of the cast aluminum made with the corrected mold.